Nation-building Under the Societal Security Dilemma: the Case of Macedonia - Sazdovski, Aleksandar (Journal of Regional Security, 2018)
In 2009, the Government of the Republic of Macedonia announced the Skopje 2014 Project, a project that envisioned an urban reconstruction of the city through a series of monuments of historical and religious figures, as well as various public buildings resembling neo-classical, or neo-baroque style. The Project was the culmination of a wider nation-building project initiated several years earlier that became known as “antiquisation” that sought to reconstruct and redefine Macedonian national identity, in which the uppermost importance was given to the figure of Alexander the Great. The nation-building project stressed a linear continuity of Macedonian national identity from antiquity to the present thereby emphasizing the nation’s unceasing existence and affirmation throughout the centuries. But what were the underlying causes that shaped the nation-building project? How have historical, political and other factors influenced the nation-building project in Macedonia? And why was ancient Macedonia chosen as the narrative around which the nation-building project could take place? These are the questions that the present article will attempt to answer. The aim of this article is to examine the complex interplay between security policy and nation-building, in the Macedonian context. More specifically, it will argue that the current nation-building project in Macedonia has been developed as a response to internal and external perceived identity threats. Namely, ever since declaring independence the Republic of Macedonia has been facing a double societal security dilemma – an external, stemming from the country’s immediate neighbors who constantly dispute the existence of a distinct Macedonian national identity, and an internal reflected in the constant challenges of the character of the State, by the country’s ethnic Albanian community. In response, the nation-building project sought to address these concerns.